2023
DOI: 10.46827/ejel.v8i1.4685
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Method to Explore the Critical Issues of Speaking Anxiety Amongst Chinese PHD Candidates’ Doctoral Dissertation Oral Defense

Abstract: Anxiety has a significant effect on oral communication, particularly when it occurs in the form of a public address. The quality of a public academic speaker's oral presentation may highly be determined by a variety of emotive elements. However, this has received much too little attention in the realm of academic dissertation oral defense presentations, despite the fact that this process may be incredibly nerve-wracking for both novice and experienced postgraduates, EFL learners in particular. In the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The main advantages of Thailand lie in its low cost, geographical location, highquality campus facilities, and welcoming attitude towards outsiders, while the quality of many international projects in Thailand is often related to low English proficiency (Viseshiri et al, 2023). Research has shown that doctoral students from China who use English as a foreign language exhibit statistically significant levels of anxiety in public speaking (Wei & Chang, 2023). The research results indicate that international graduate students who speak non English as their mother tongue face difficulties in academic writing, especially when it comes to English as the language of instruction (Singh & Kaur, 2016).…”
Section: Language Barriersmentioning
confidence: 93%
“…The main advantages of Thailand lie in its low cost, geographical location, highquality campus facilities, and welcoming attitude towards outsiders, while the quality of many international projects in Thailand is often related to low English proficiency (Viseshiri et al, 2023). Research has shown that doctoral students from China who use English as a foreign language exhibit statistically significant levels of anxiety in public speaking (Wei & Chang, 2023). The research results indicate that international graduate students who speak non English as their mother tongue face difficulties in academic writing, especially when it comes to English as the language of instruction (Singh & Kaur, 2016).…”
Section: Language Barriersmentioning
confidence: 93%